Effect of restrticted feeding on productivity of Mojosari x Alabio cross-bred layer ducks (MA): 1. First phase of laying 20-43 weeks old - Pius P Ketaren; L.H Prasetyo (Jurnal Ilmu Ternak dan Veteriner, 2002)
Feed cost is the major cost for duck-egg production which accounted to be more than 70% of total production cost. Feed efficiency of duck-egg production in Indonesia is low. The main reasons for the low feed efficiency (high feed conversion ratio, FCR) are (1) genetic trait (2) high feed wastage and (3) inadequate nutrient content of diet. An experiment was conducted to evaluate effect of restricted feeding of pelleted diet on Mojosari x Alabio (MA) cross-bred duck performances from 20-43 weeks old. The experiment was designed in a Completely Randomized Design. 156 MA cross-bred ducks were devided into three groups and fed three experimental diets: (1) 70%, 85%. and ad libitum. All experimental diets were fed to ducks for 24 weeks and feed intake, egg production, egg weight, FCR, molting and egg quality: egg yolk weight, albumen wight, egg shell weight and egg yolk colour score were measured as parameters. The results showed that the restricted feeding of 70% and 85% significantly (P<0.05) reduced egg production, egg weight and induced early molting but did not adversely affect duck livability and egg quality. MA croos-bred duck was more efficient by feeding ad libitum than the restricted feeding. FCR of duck fed 70% (6.38) was significantly (P<0.05) worst compared to FCR of duck fed 85% (3.68) and ad libitum (2.88).   Key words: Restricted feeding, MA crossbred duck, productivity and egg quality